EVALUATION OF USER SATISFACTION USING THE PIECES FRAMEWORK IN THE TEMAN BUS APPLICATION - Arakian, Laurensia Anjelina Tutosili; Darmawiguna, I Gede Mahendra; Indradewi, I Gusti Ayu Agung Diatri (LPPM Universitas Nusa Mandiri, 2023)
The TEMAN BUS program employs technology to improve road-based public transportation in urban areas. The Ministry of Transportation of the Republic of Indonesia implements digital transformation by developing the TEMAN BUS application to support TEMAN BUS transportation services. Passengers will find it more straightforward with this application to access the TEMAN BUS travel route, view information about the departure timetable, and observe bus arrivals in real time. To evaluate an application's effectiveness, it is necessary to assess the user's impression when the program is launched. This study uses the PIECES Framework, which has six variables Performance, Information, Economics, Control and Security, Efficiency, and Service, to assess how users perceive the TEMAN BUS application. The findings of this study were derived from the perceptions of respondents, who felt that information and data performance, control and security, service, and user satisfaction were not good, and from the findings of hypothesis testing, which suggested that information and data performance and user satisfaction were unrelated.